Design and implementation of an FPGA-based GPR and TDR system for soil investigations - De Joya, Roberto D. Jr.; Mogatas, Paula Angelica P.; Purisima, Miguel Carlo L.; Salazar, Carmela A. (2010)
Ground penetrating radar (GPR) has been favored as a tool for subsurface investigations because of its non-destructive nature and faster survey times than traditional methods such as strip mapping and site excavation.Time Domain Reflectometry (TDR), on the other hand, has already been established as an effective tool in locating faults in power and communication cables. It also has been proven to have some degree of success in monitoring slope movement, typically by detecting reflections from discontinuities along grouted coaxial cables buried in the ground. A compact FPGA-based GPR and TDR system for soil investigations was designed and implemented. The similarity in the operation of impulse GPR and TDR systems facilitated the implementation of both using a single impulse generator and receiver unit on Altera Stratix EP1S25 FPGA.Implementation on an FPGA provides a more flexible alternative than hardware-based configurations. The system was designed such that the impulse generator and receiver can be ported either to a GPR bow-tie antenna pair or to a semi-rigid TDR cable assembly. GPR bow-tie antennas were designed to suit pulse radiation at the frequency band of interest. TDR cable prototypes were constructed based on a novel design using a sponge dielectric that maximizes the sensitivity of the cable response to abrupt bends. Received signal data from FPGA is downloaded to a PC via RS-232. GPR A-scans and TDR cable responses were plotted in Matlab. Free space tests for the GPR mode of system were conducted. The GPR tests showed that the system was able to detect metal reflectors placed in front of the antennas. The TDR sponge cable was, however, not feasible to use with the system since the minimum pulse width that the FPGA can generate requires a very long cable to be able to show discontinuities on the cable. Hence, RG-58U cables were used to conduct tests for the TDR mode of the system. The TDR tests showed that the system was able to detect induced discontinuities on RG-58U cables. Experimental results show that the GPR/TDR system is functional. The system has demonstrated the feasibility of implementing a combined GPR and TDR system on a single FPGA platform with minimal external hardware components. However, hardware constraints of the currently available Altera Stratix EP1S25 development board hindered the system's effectiveness for practical applications. Better hardware specifications are recommended to reach the full potential of the system. The successful development of the system is foreseen to provide a potential test bed for further studies particularly on processing algorithms and other antenna and cable improvements.
Thesis (B.S. Electronics and Communications Engineering) -- University of the Philippines, Diliman
Keywords: Ground penetrating radar -- Design and construction; Time-domain reflectometry -- Design and construction; Field programmable gate arrays; Altera Stratix EP1S25.